2017
DOI: 10.1175/jcli-d-16-0483.1
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cloud, Boundary Layer, and Sea Ice Interactions over the Southern Ocean during Winter

Abstract: During austral winter, a sharp contrast in low-cloud fraction and boundary layer structure across the Antarctic sea ice edge is seen in ship-based measurements and in active satellite retrievals from Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observations (CALIPSO), which provide an unprecedented view of polar clouds during winter. Sea ice inhibits heat and moisture transport from the ocean to the atmosphere, and, as a result, the boundary layer is cold, stable, and clear over sea ice and warm, mois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 52 publications
7
30
0
Order By: Relevance
“…The number concentration of Antarctic aerosols -of which the INPs will be a subset -has been shown to have a seasonal cycle that is well documented. For instance, Weller et al (2011) and Kim et al (2017) documented the monthly variation in the total aerosol concentration at the coast in the Weddell Sea sector (Neumayer Station) and at the northern tip of the Antarctic Peninsula (King Sejong Station), respectively. They found that the maximum concentrations occurred in February (Kim et al, 2017, their Fig.…”
Section: On the Marine Origin Of The (Biological) Inpsmentioning
confidence: 99%
“…The number concentration of Antarctic aerosols -of which the INPs will be a subset -has been shown to have a seasonal cycle that is well documented. For instance, Weller et al (2011) and Kim et al (2017) documented the monthly variation in the total aerosol concentration at the coast in the Weddell Sea sector (Neumayer Station) and at the northern tip of the Antarctic Peninsula (King Sejong Station), respectively. They found that the maximum concentrations occurred in February (Kim et al, 2017, their Fig.…”
Section: On the Marine Origin Of The (Biological) Inpsmentioning
confidence: 99%
“…The relationship between clouds and sea ice also differs by season. In winter and fall, there is an apparent increase in low cloud cover with decreasing sea ice concentration (as in Wall, Kohyama, et al, 2017). During spring and summer, low cloud cover does not appear as closely related to sea ice concentration.…”
Section: Seasonal Sea Ice Concentration and Low Cloud Covermentioning
confidence: 99%
“…Surface-independent observations of temperature and cloud phase help constrain potential mechanisms underlying the observed cloud response to varying sea ice conditions. One potential mechanism leading to increased cloud opacity when sea ice retreats is an increase in air-sea coupling strength (Kay & Gettelman, 2009;Morrison et al, 2018;Wall, Kohyama, et al, 2017). Air-sea coupling contributes to low cloud formation and maintenance as moisture is transferred from the sea surface to the atmosphere to promote cloud formation (Klein & Hartmann, 1993).…”
Section: Potential Mechanisms For Increasing Opaque Cloud Fractionmentioning
confidence: 99%
“…Ra phael (2003) demonstrated the Southern Hemisphere atmospheric response to the summertime sea-ice in crease over the entire Antarctic using a CGCM. More recently, by analyzing observational data and CGCM model output, Wall et al (2017) revealed that the atmospheric boundary layer in the Weddell Sea is stable over the sea ice during austral winter because sea ice inhibits heat and moisture transport from the ocean to the atmosphere, while the boundary layer is unstable and cloudy over open water.…”
Section: Introductionmentioning
confidence: 99%